Surface microhardness of nanohybrid and microhybrid composite resins light cured at different distances - Zuloeta-Navarro Luz Clarita; Orrego-Ferreyros Luis Alexander (Mashhad University of Medical Sciences, 2023)
Objective: This study aimed to compare the surface microhardness of a nanohybrid and a microhybrid resin composite light-cured at two different distances.Methods: A total of 40 disc specimens were prepared for this in vitro experiment; 20 from a nanohybrid composite resin (Filtek P60; 3M ESPE) and 20 from a microhybrid composite resin (Filtek Z250; 3M ESPE). Each group was divided into two equal subgroups (n=10), based on the distance between the light-curing device and the composite surface (either 2 or 4 mm). After 24 hours of curing, the teeth underwent the microhardness test to determine the Vickers hardness number (VHN) at the surface. The data were subjected to statistical analysis using a two-way analysis of variance (ANOVA) at the significance level of P<0.05.Results: The nanohybrid resin composite showed higher microhardness values than the microhybrid resin at both 2 mm and 4 mm distances, although the difference between the two groups was only significant at the distance of 4 mm (P = 0.017). No significant difference was observed in the nanohybrid composite resin between the two curing distances (P = 0.151). However, the hardness of the microhybrid composite decreased significantly with increasing the curing distance from 2 to 4 mm (P = 0.015).Conclusions: This study reveals that light-curing distance significantly affects the microhardness of microhybrid composite resin. The nanohybrid composite showed comparable hardness up to the distance of 4 mm, indicating its suitability to be used in situations where a close curing distance cannot be achieved.